ANALISA RANTAI PASOK DAN HARGA POKOK PENJUALAN TELUR AYAM RAS PADA PASAR WAY HALIM BANDAR LAMPUNG - Susanti Sundari (Fakultas Teknik Universitas Tulang Bawang Lampung, 2018)
The race chicken eggs are one of the commodities that have an important role in supporting the availability of animal protein for the community. The average price of egg is unstable, the length of the supply chain affects the price until to the final consumer. The research with the title of Supply Chain Analysis and Cost of Goods Sold of chicken egg at Way Halim market Bandar Lampung, it has problems : (1). How the supply chain of chicken egg at Way Halim market in Bandar Lampung, (2). How much the Cost of Goods Sold of chicken egg at Way Halim market in Bandar Lampung. This study aims (1). To know the supply chain of chicken egg at Way Halim market in Bandar Lampung, (2) to know how much the Cost of Goods Sold of chicken egg at Way Halim market in Bandar Lampung. The determination of location is selected purposively, that is at Way Halim market in Bandar Lampung. And the sample determination is taken by random sampling method to determine the sample of supply chain players where research respondents are the players who involve in the supply chain activity of chicken egg at Way Halim market in Bandar Lampung. And the data collection was conducted during early March 2018 with the results of the research are (1).The Chain of chicken egg supply that occurs in Way Halim Bandar Lampung market is relatively short, that is from chicken egg breeder supplier to agent, to trader and trader to end consumer. (2).The amount of profit earned by depends also on the price set by Pinsar (Association of People's Poultry Insan). Keywords: Race Chicken Egg, Way Halim Market Bandar Lampung, Supply chain, Cost of Goods Sold.